A Thematic Analysis of the First-Time Users of E-Money Transactions - Nassar Nordin; Syahidawati Hj. Shahwan; Norhazlina Ibrahim; Nurulbahiah Awang (Asian Scholars Network, 2024)
International Journal of Business and Technology Management Volume 5 No.4 Page (190-200)